Let's simplify \( 1,000^{23} \).
First, we know that \( 1,000 = 10^3 \).
So we can re-write \( 1,000^{23} \) as follows:
\[ 1,000^{23} = (10^3)^{23} \]
Now, using the power of a power property in exponents, we multiply the exponents:
\[ (10^3)^{23} = 10^{3 \times 23} = 10^{69} \]
Thus, \( 1,000^{23} = 10^{69} \).
Now let's evaluate the claims made by Charles, Zayeer, and Kali:
- Charles says the correct simplification is 10 - this is incorrect because \( 1,000^{23} = 10^{69} \).
- Zayeer says the correct simplification is 1,000 - this is also incorrect for the same reason.
- Kali says the correct simplification is 100 - again, this is incorrect.
Since none of them correctly simplified \( 1,000^{23} \), the correct response is:
none of them.